Lefamulin - a recently developed antibiotic for treatment of community-acquired bacterial pneumonia (CABP) - Leila Abod; Natalia Ilnicka; Daria Matyja; Maria Sadlik; Patrycja Zuziak (Kazimierz Wielki University, 2023)
Introduction and aim. Nowadays, the increasing resistance of bacteria is a concerning and challenging issue in terms of effective treatment of bacterial infections. The amount of available antibiotics has been quite constant for many years. The search for substances alternative to older classes of drugs, among which resistance is growing, has been ongoing for years. One of the newly introduced available alternatives is lefamulin. The aim of this paper is to present the potential benefits of its use in comunity-acquired bacterial pneumonia (CABP).  Material and methods. A review of the available literature was performed by searching the PubMed and GoogleScholar databases using the following key words: lefamulin; BC3781; pleuromutilin; CABP; community acquired pneumonia. Analysis of literature. Lefamulin is a bacteriostatic antibiotic from the group of pleuromutilins, which has a unique mechanism of action consisting in binding to the bacterial 50S ribosomal subunit in the peptidyl transferase center. Thanks to this, it rarely causes resistance among other groups of antibiotics and is characterized by a safe action profile. Its spectrum of action includes bacteria causing CABP. In phase III studies, the efficacy of lefamulin monotherapy was comparable to that of moxifloxacin with or without linezolid in CABP.  Thanks to broad spectrum of action its usefulness may also extend to treatment of methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus faecium, and multidrug-resistant organisms associated with sexually transmitted infections, e.g., Neisseria gonorrhoeae, Mycoplasma genitalium, although more additional clinical and pharmacodynamic data is needed. Conclusion. Lefamulin is a promising addition to the antibiotic armamentarium for treating CABP. Its unique mechanism of action, activity against typical and atypical bacteria, flexible dosing options, and favorable safety profile make it a beneficial choice for clinicians.